Culture and Civilization: Theories and Realities - Dr.Zeenat Bibi; Dr. Raheela Bibi; Dr Robina Rashid; Dr Rukhsana Bibi; Dr. Muhammad Nasir Afridi; Dr Saeed Ur Rahman; Rubina Gul; Dr Jamila Gul (Al-Qanṭara, 2024)
he identity of any nation depends on its civilization and culture. The word "Saqafat” is used in Urdu for culture. The meaning of culture is lifestyle, arts, morals and manners, rituals and traditions, philosophy and wisdom, beliefs and ideas and matters of love and family relationships. The word "Tehzeeb" is used in Urdu for civilisation. Civilization is the overall cultural, social, and intellectual formation of human life, which is based on various elements. These elements include language, religion, traditions, arts, and social structure. Language is the primary means of social communication and intellectual expression, while religion provides moral values ​​and spiritual guidance. Traditions and cultural rituals are symbols of social identity and stability. The arts, such as music, literature, and art, represent aesthetic experiences and creative expression. Social structure, including family and institutions, affects an individual's social status and interactions. The harmony and interaction of all these elements play an important role in forming and developing civilization, which is part of human society's basic identity and evolution.